Acute myocardial infarction without obstructive coronary disease secondary to toxic multinodular goiter thyrotoxicosis - Mejía Sandoval, Harvey Julián (2021)
Acute myocardial infarction in the absence of obstructive coronary artery disease (MINOCA) represents a diagnostic challenge in clinical practice. Documentation of an ischemic substrate is necessary for its diagnostic approach, with a treatment that must be specific according to the identified etiology. A group of these patients presents ischemia secondary to an alteration in the oxygen supply/demand ratio. We present the case of a female adult patient, with severe hyperthyroidism and thyrotoxicosis, who develops an acute coronary syndrome, with elevated troponin T and normal coronary arteries on coronariography. Treatment was aimed at treating the triggering cause, initially pharmacologically and later surgically, with a total resolution of the condition, symptomatic improvement in the patient, and a decrease in cardiac biomarkers.